Solid Tumor Complicated With Venous Thromboembolism: A 10-Year Retrospective Cross-Sectional Study. (12th February 2021) - Peng, Miao; Yang, Shengli; Li, Guiling; Zhang, Tao; Qin, Xiaojuan; Shi, Chen; Chang, Jian; Chen, Mengni; Chen, Chen; Li, Bingjie; Cao, Sihang; Li, Ting; et al.
Venous thromboembolism (VTE), including pulmonary embolism (PE) and deep vein thrombosis (DVT) occurs more frequently in cancer patients than in the general population. A retrospective cross-sectional study was carried out in patients with solid tumor complicated with VTE admitted to the Cancer Center, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology between January 1st, 2008 and December 31th, 2017. The incidence of VTE in hospitalized cancer patients was 1.8%, twice the incidence of VTE in hospitalized non-cancer patients. The annual incidence of cancer-associated VTE in our center varied between 1.6% in 2015 and 0.4% in 2009 with an overall average incidence of 1.3% over the research decade. BMI values of 549(67.7%) cancer patients were within the normal range, but none of patients had BMI greater than 35 kg/m 2 . 747(92.1%) cancer patients had ECOG PS score ≤ 2 and 481(59.3%) had distant metastasis. Patients with pancreatic, bladder, ovarian and endometrial cancer had the highest incidence of VTE. Upper extremity DVT (47.2%) was more common in cancer patients and might be closely associated with CVC (74.9%), while lower extremities DVT (36.1%) intended to PE development (15.0%). The annual incidence rates showed a fluctuating and upward trend over the research decade. VTE occurrence was closely related to tumor stage, tumor site, catheterization and anti-neoplasm therapy in cancer patients.